Employee Work Competence In Improving Organisational Performance At The Regional Secretariat Of Buton Regency - La didi; Urfin, Urfin; Asmiddin, Asmiddin (Jurnal Scientia, 2024)
This research aims to describe this Research Proposal regarding Employee Work Competence in Improving Organisational Performance at the Regional Secretariat of Buton Regency. This research uses a qualitative descriptive design that collects data by means of observation, interviews with informants. The data is tabulated as needed and then the data is analysed qualitatively descriptively including data reduction, data presentation and conclusion drawing so that it can produce an understanding and is proven by data analysis techniques and the validity of the data findings. The results of this study indicate that to see employee competence in improving organisational performance at the Regional Secretariat of Buton Regency according to Spencer and Spencer in Wibowo (2016: 273) competence is formed from five indicators: (1) Motives, (2) Traits, (3) Self-Concept, (4) Knowledge, (5) Skills. Thus, the goal of achieving employee performance competence in carrying out the performance of the regional secretariat of Buton Regency will be realised. It is suggested that the performance of employees at the Regional Secretariat Office of Buton Regency can be further improved by training and courses for employees so that employees at the Regional Secretariat Office of Buton Regency can become employees who have a good level of competence and can maximise employee performance, the Buton Regency Government must pay more attention to the quality of human resources of employees at the Regional Secretariat Office of Buton Regency by providing training to employees in order to improve employee competence, improving the governance system (management) of government affairs and community services by optimising the use of information and communication technology.